2021
DOI: 10.3390/md19060346
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Protects Dendritic Cells from Lipopolysaccharide-Induced Immune Dysfunction

Abstract: Astaxanthin, originating from seafood, is a naturally occurring red carotenoid pigment. Previous studies have focused on its antioxidant properties; however, whether astaxanthin possesses a desired anti-inflammatory characteristic to regulate the dendritic cells (DCs) for sepsis therapy remains unknown. Here, we explored the effects of astaxanthin on the immune functions of murine DCs. Our results showed that astaxanthin reduced the expressions of LPS-induced inflammatory cytokines (TNF-α, IL-6, and IL-10) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…TGF-β is required for IL-17 to produce T helper cell (Th-17 cell) differentiation [ 52 ]. In our data, astaxanthin reduced the production of IL-1β, IL-17, and TGF-β in LPS-induced DCs and in LPS-challenged mice, which is in line with our previous findings that showed a decrease in TNF-α, IL-6, and IL-10 caused by astaxanthin in an LPS-induced DC model [ 31 ]. These data suggest that astaxanthin, as an antioxidant, can effectively mitigate overloaded cytokine production in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…TGF-β is required for IL-17 to produce T helper cell (Th-17 cell) differentiation [ 52 ]. In our data, astaxanthin reduced the production of IL-1β, IL-17, and TGF-β in LPS-induced DCs and in LPS-challenged mice, which is in line with our previous findings that showed a decrease in TNF-α, IL-6, and IL-10 caused by astaxanthin in an LPS-induced DC model [ 31 ]. These data suggest that astaxanthin, as an antioxidant, can effectively mitigate overloaded cytokine production in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we found that astaxanthin strongly inhibited the immune dysfunction of DCs induced by LPS [ 31 ]. Here, our work further shows the antioxidative effects of astaxanthin in DCs and mice, which is a potential key aspect of inflammatory control in the sepsis model ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, CD69 was detected as a critical activation marker of DCs [23]. The results showed that the expression of CD69 in DCs was remarkably increased after treatment with riboflavin for 24 h (Figure 5A,B).…”
Section: Riboflavin Enhanced the Cytokine Production Of Dcsmentioning
confidence: 91%
“…Marine carotenoids exert strong antioxidant, restorative, antiproliferative and anti-inflammatory effects and can be used both as skin photoprotection to inhibit the negative effects of solar UV radiation and as nutraceutical/cosmeceutical ingredients to prevent oxidative stress-related diseases. In this regard, Yin et al (2021) contributed with the publication of two research articles focused on the biological properties of astaxanthin, a naturally occurring red carotenoid pigment classified as xanthophyll native to marine organisms, such as microalgae and seafood, with known potent antioxidant properties [5,6]. The authors evaluated the anti-inflammatory and antioxidant capacity of astaxanthin on the immune functions of murine dendritic cells (DCs) in a sepsis model.…”
mentioning
confidence: 99%